Considering hate : violence, goodness, and justice in American culture and politics - Whitlock, Kay.; Bronski, Michael (Boston, Massachusetts : Beacon Press, 2015)
"Hate haunts the human imagination. As a society, the United States has created a "hate frame" through which we view the world. It provides a concept, a language, and a set of cultural images and narratives that help us attribute motivation for violence, slot different segments of the population into tidy categories of "us" and "them," and justify enmity. Violence against marginalized and vulnerable communities - people of color, queers, women, people with disabilities, Muslims, and Jews - is said to be the result of hate, and the most popular remedy for it is more policing and harsher punishments. But is hate the right diagnosis for the violence that is so prevalent in American society? Does it help us reduce or prevent violence? How does it shape our understanding of innocence, guilt, and justice? How does it influence the way we assign people into the roles of "victim" and "perpetrator"? Considering Hate makes the case that the hate frame distorts our understanding of violence directed against vulnerable groups, obscures our ability to trace that violence to its sources, and impedes our ability to address the conditions that produce it. By anchoring us to simplistic political and cultural notions about violence and justice, the hate frame may do more harm than good."--Publisher information.
Dehumanization and violence -- Hate in the public imagination -- Boundaries, borders, and psychic shadows of hate -- Collective responsibility and moral disengagement -- Goodness in the public imagination.
Includes bibliographical references and index.
Keywords: Hate -- United States; Violence -- United States; Discrimination -- United States; Multiculturalism -- United States; United States -- Race relations; SOCIAL SCIENCE -- Discrimination & Race Relations; Discrimination; Hate; Multiculturalism; Race relations; Violence; United States